Efficient Feedforward Linearization Technique Using Genetic Algorithms for OFDM Systems. (8th March 2010) - García García, Paloma Paloma; Mingo Mingo, Jesús de Jesús de; Carro Carro, Pedro Luis Pedro Luis; Valdovinos Valdovinos, Antonio Antonio
Abstract : Feedforward is a linearization method that simultaneously offers wide bandwidth and good intermodulation distortion suppression; so it is a good choice for Orthogonal Frequency Division Multiplexing (OFDM) systems. Feedforward structure consists of two loops, being necessary an accurate adjustment between them along the time, and when temperature, environmental, or operating changes are produced. Amplitude and phase imbalances of the circuit elements in both loops produce mismatched effects that lead to degrade its performance. A method is proposed to compensate these mismatches, introducing two complex coefficients calculated by means of a genetic algorithm. A full study is carried out to choose the optimal parameters of the genetic algorithm applied to wideband systems based on OFDM technologies, which are very sensitive to nonlinear distortions. The method functionality has been verified by means of simulation.